2018
DOI: 10.1002/mds.27501
|View full text |Cite
|
Sign up to set email alerts
|

PTRHD1 Loss‐of‐function mutation in an african family with juvenile‐onset Parkinsonism and intellectual disability

Abstract: Background: The genetic bases of PD in sub‐Saharan African (SSA) populations remain poorly characterized, and analysis of SSA families with PD might lead to the discovery of novel disease‐related genes. Objectives: To investigate the clinical features and identify the disease‐causing gene in a black South African family with 3 members affected by juvenile‐onset parkinsonism and intellectual disability. Methods: Clinical evaluation, neuroimaging studies, whole‐exome sequencing, homozygosity mapping, two‐point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 15 publications
1
14
4
Order By: Relevance
“…PTRHD1 is a protein of unknown function, which lacks its eponymous activity: although it binds peptidyl-t-RNA, it does not hydrolyze it (Burks et al, 2016). The role of PTRHD1 in autosomal recessive Parkinson's disease is supported by two additional reports: an adjacent mutation (H53Y) was found in Iranian patients (Khodadadi et al, 2017), and mutations in PTRHD1, which result in truncation of the protein, were identified in African patients (Kuipers et al, 2018). There are two arguments that support a pathogenic role of A 1 R-G279S 7.44 .…”
Section: Discussionmentioning
confidence: 97%
“…PTRHD1 is a protein of unknown function, which lacks its eponymous activity: although it binds peptidyl-t-RNA, it does not hydrolyze it (Burks et al, 2016). The role of PTRHD1 in autosomal recessive Parkinson's disease is supported by two additional reports: an adjacent mutation (H53Y) was found in Iranian patients (Khodadadi et al, 2017), and mutations in PTRHD1, which result in truncation of the protein, were identified in African patients (Kuipers et al, 2018). There are two arguments that support a pathogenic role of A 1 R-G279S 7.44 .…”
Section: Discussionmentioning
confidence: 97%
“…Similar symptoms, including intellectual disability/attention deficits and, successively, gait disturbance, bradykinesia, tremor and falls, have also been reported in two male siblings from another Iranian family, homozygous carriers of a PTRHD1 c.155G>A (p.Cys52Tyr) variant (Jaberi et al, 2016). Likewise, the study on the Sub-Saharan Xhosa-speaking community showed that, within the same family, three homozygous carriers of a PTRHD1 deletion (c.169_196del, p.Ala57Argfs*26) had mental disability and symptoms of parkinsonism, with a wider clinical variability compared to the two previous studies (one member showed just tremor, one just bradykinesia and hypokinesia, one both) (Kuipers et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Three family studies nominated peptidyl-tRNA hydrolase domain containing 1 gene ( PTRHD1 ) as a possible disease-causing gene in atypical parkinsonism (Jaberi et al, 2016; Khodadadi et al, 2017; Kuipers et al, 2018). In these studies, two conducted in Iranian families (Jaberi et al, 2016; Khodadadi et al, 2017) and one in a specific sub-Saharan African community (Kuipers et al, 2018), the carriers showed some level of early onset cognitive impairment, and later developed symptoms of parkinsonism. In particular, homozygous PTRHD1 c.157C>T (p.His53Tyr) variants were detected in two Iranian siblings with intellectual disability and motor abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…The group has identified pathogenic mutations, albeit at low frequencies, in all of the commonly associated PD genes, as elaborated on in the next section. Recently, a PTRHD1 mutation was identified in a Xhosa family with Parkinsonism and intellectual disability (40).…”
Section: South Africamentioning
confidence: 99%
“…On the African continent, most of the work has been done on patients from North African Arabic countries where the frequency of the LRRK2 G2019S mutation was reported to be as high as 41% of patients (44) due to the presence of genetic founder effects. A number of studies have been conducted in South Africa but the mutation detection rate has been low (32,40,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The other studies have been done in Nigeria (30)(31)(32), Tanzania (12), Zambia (56), and Ghana (57) but for the vast majority of the countries in Africa, no genetic studies have been reported.…”
Section: Genetics Of Pd In African Populationsmentioning
confidence: 99%